Cell-Mediated Immunity in Humans During Viral Infection I. Effect of Rubella on Dermal Hypersensitivity, Phytohemagglutinin Response, and T Lymphocyte Numbers - Kauffman, Carol A. (1974)
Phytohemagglutinin-induced lymphocyte deoxyribonucleic acid synthesis, dermal hypersensitivity, and peripheral blood thymus-derived lymphocyte numbers were assessed in nine men with experimentally induced rubella infection. Five of these men and two additional volunteers received treatment with tilorone dihydrochloride, an antiviral drug. Response to phytohemagglutinin was not changed during rubella; T lymphocyte numbers in peripheral blood were not influenced by the viral illness. However, dermal hypersensitivity was markedly impaired in all volunteers during the height of the illness. Tilorone alone, or with rubella, had no effect on any of the parameters studied.